Quantitative analysis of environment potential for cluster development in tourist regions of Slovak Republic - Gáll, Jozef; Strežo, Marek (Geographica Pannonica, 2019)
Clusters and cluster initiatives are the most effective interconnection not only between companies of a particular industry but also in the wider surroundings where cooperation is the most important factor. The analysis of potential clusters provides a clear picture of the regional economy and is one of the backgrounds in formulating the economic development strategies of the regions. The main aim of this article is to propose the appropriate location of the potential tourism cluster. To achieve this, it is necessary to identify the activity of the tourism sector in the selected regions that create the conditions for cluster formation. The identification is done using quantitative cluster mapping methods – the location quotient and shift-share analysis. The main sources of the calculations are statistical data on employment published by the Statistical Office of the Slovak Republic. Comparing tourist regions has helped identify not only growing but also decreasing potential cluster organizations. The application of both methods has found that the region of Upper Považie region is, with his positive dynamic development, positive location quotient values and the support of local factors, the most appropriate region for the location of the tourism cluster. The results achieved can be used in further assessments of the environment and his effectiveness for cluster creation already in the specific tourist region. In this process it is necessary to involve institutions that know the environment and can assess the importance of tourism for the region.
Keywords: cluster identification; location quotient; shift-share analysis; tourist regions of Slovakia